ANALISIS KEAUSAN DAN WAKTU PENGEREMAN KAMPAS CAKRAM ASBESTOS DAN NON ASBESTOS DENGAN VARIASI BEBAN PENGEREMAN DAN BERAT PENGENDARA PADA SEPEDA MOTOR HONDA SUPRA X 125 CC - Ali Mulahela, Sayid Khaidir; Catur, Agus Dwi; Pandiatmi, Pandri (Universitas Mataram, 2015)
Brake system is an important thing of vehicle. Many kinds of brake pads presents by each factory. Brake pads made of asbestos and non asbestos material. Each of them have excess and lack. This research aims to know the performance of each type of brake pads so that it can show the excess and lack of each type of product. As user, we have to choose a product which will be used in our vehicle cleverly.The research be done by giving variations in load of brake and weight of rider at a constant speed. The load of brake used spring with the variation are 2 kg, 3 kg and 4kg. While, weight rider are varied with 54 kg and 111 kg.Research result shows that increasing load of pull brake led to increasing the value of worn out and a decline in the braking time, while increasing weight of the rider causes an increase in the value of worn out and braking time at all types of brake pad products. In dry condition, the lowest wear is 1,37x10-4 mm/second in non asbestos pads and the highest wear is 3,088x10-5 mm/second in asbestos pads. While, the smallest braking time is 28,79 seconds in asbestos pads and the biggest is 64,26 seconds in non asbestos pads. In wet condition, the lowest wear is 2,422x10-5 mm/second in asbestos pads and the highest wear is 7,716x10-5mm/second in non asbestos pads. While, the smallest braking time is 29,46 seconds in non asbestos pads and the biggest is 62,71 seconds in asbestos pads.